The Da’wah Communication Strategy of Jamaah Tabligh in Sub-district of Tondo, Palu City - Nuraedah Nuraedah; Mutawakkil Mutawakkil (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2020)
This study aims to analyze the da'wah communication strategy of Jamaah Tabligh that includes planning, implementing and identifying agents of change in the Jamaah da’wah in sub-district of Tondo, Palu. The research used phenomenological method with interviews and observations as data collection techniques. The results showed that Jamaah Tabligh da’wah communication strategies include; first, planning with tafakud which means ensuring readiness. Second, the implementation of da'wah through khuruj emphasizes the practice of Intiqoli (Amal Intiqoli) and the practice of maqami (Amal maqami). Third, the agents of change in the da'wah communication process are individuals and groups. The Agents referred to are ahbab karkun and amir. The role of the changer is to change morals to be praiseworthy according to the guidance of the Prophet Muhammad SAW.Penelitian ini bertujuan menganalisis strategi komunikasi dakwah yang mencakup perencanaan, pelaksanaan dan mengidentifikasi agen perubahan dakwah Jamaah Tabligh di Tondo, Kota Palu. Metode penelitian yang digunakan adalah metode fenomenologi dengan wawancara dan observasi sebagai teknik pengumpulan data. Hasil penelitian menunjukkan bahwa strategi komunikasi dakwah Jamaah Tabligh meliputi; pertama perencanaan dengan tafakud yaitu memastikan kesiapan. Kedua pelaksanaan dakwah melalui khuruj, dengan memperhatikan amalan Intiqoli dan amalan maqami. Ketiga, agen pengubah dalam proses komunikasi dakwah Jamaah Tabligh yakni individu dan kelompok. Agen pengubah yang dimaksud adalah ahbab karkun dan amir. Peran pengubah ialah merubah akhlak menjadi terpuji sesuai tuntunan Rasulullah SAW.